Tidal - Hocking, Amanda (A watersong novel, 2013)
With Penn and Lexi determined to kill Gemma and replace her with another siren, Gemma, aided by Harper and Daniel, must delve into her enemies' mythical past and darkest secrets in a last-ditch effort to protect all that she holds dear.